Optimalisasi Keuntungan Kopi Jawara Menggunakan Pemrograman Linear Melalui Metode Simpleks - Anastasya Anastasya; Anggi Julita; VALENTINUS VALLY (CV. AKIRA JAVA BULU, 2026)
This study aims to optimize the profit of the Jawara Coffee Micro, Small, and Medium Enterprise (MSME) by employing linear programming with the simplex method. This MSME faces challenges in determining the optimal production combination to maximize their profit with limited resources. In the production process of Jawara Coffee, this research identified decision variables, an objective function, and constraints. Production costs, selling prices, production capacity, market demand, andother relevant data were collected. Subsequently, a linear programming model was constructed and solved using the simplex method to determine the optimal production combination. This study demonstrates that the application of the simplex method can provide a significant optimal solution to enhance the profitability of the Jawara Coffee MSME. Furthermore, this research offers valuable insights and recommendations for the Jawara Coffee MSME to improve their operational efficiency and profitability amidst intense market competition.